Pin1, a new player in the fate of HIF-1α degradation: an hypothetical mechanism inside vascular damage as Alzheimer’s disease risk factor - Lonati, Elena; Brambilla, Anna; Milani, Chiara; Masserini, Massimo; Palestini, Paola; Bulbarelli, Alessandra (Frontiers in Cellular Neuroscience, 2014)
Aetiology of neurodegenerative mechanisms underlying Alzheimer's disease (AD) are still under elucidation. The contribution of cerebrovascular deficiencies (such as cerebral ischemia/stroke) has been strongly endorsed in recent years. Reduction of blood supply leading to hypoxic condition is known to activate cellular responses mainly controlled by hypoxia-inducible transcription factor-1 (HIF-1). Thus alterations of oxygen responsive HIF-1α subunit in the central nervous system may contribute to the cognitive decline, especially influencing mechanisms associated to APP (amyloid precursor protein) amyloidogenic metabolism. Although HIF-1α protein level is known to be regulated by von Hippel-Lindau (VHL) ubiquitin-proteasome system, it has been recently suggested that Gsk-3β (glycogen synthase kinase-3β) promotes a VHL-independent HIF-1α degradation. Here we provide evidences that in rat primary hippocampal cell cultures, HIF-1α degradation might be mediated by a synergic action of Gsk-3β and Pin1 (peptidyl-prolyl cis/trans isomerase). In post-ischemic conditions, such as those mimicked with oxygen glucose deprivation (OGD), HIF-1α protein level increases remaining unexpectedly high for long time after normal condition restoration jointly with the increase of LDH (lactate dehydrogenase) and BACE1 (β-secretase 1) protein expression (70% and 140% respectively). Interestingly the Pin1 activity decreases about 40%-60% and Pin1S16 inhibitory phosphorylation significantly increases, indicating that Pin1 binding to its substrate and enzymatic activity are reduced by treatment. Co-immunoprecipitation experiments demonstrate that HIF-1α/Pin1 in normoxia are associated, and that in presence of specific Pin1 and Gsk-3β inhibitors their interaction is reduced in parallel to an increase of HIF-1α protein level. Thus we suggest that in post-OGD neurons the high level of HIF-1α might be due to Pin1 binding ability and activity reduction which affects HIF-1α degradation: an event